2020
DOI: 10.1002/chem.201903936
|View full text |Cite
|
Sign up to set email alerts
|

A Quadrupolar Bis‐Triarylborane Chromophore as a Fluorimetric and Chirooptic Probe for Simultaneous and Selective Sensing of DNA, RNA and Proteins

Abstract: A water‐soluble tetracationic quadrupolar bis‐triarylborane chromophore showed strong binding to ds‐DNA, ds‐RNA, ss‐RNA, as well as to the naturally most abundant protein, BSA. The novel dye can distinguish between DNA/RNA and BSA by fluorescence emission separated by Δtrueν˜ =3600 cm−1, allowing for the simultaneous quantification of DNA/RNA and protein (BSA) in a mixture. The applicability of such fluorimetric differentiation in vitro was demonstrated, strongly supporting a protein‐like target as a dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 70 publications
7
42
2
Order By: Relevance
“…All four compounds bind to dsDNA/RNA and ssDNA/RNA with similar affinities; this contrasts with the fact that binding affinities for single‐stranded polynucleotides are typically 2–3 orders of magnitude lower than for double‐stranded polynucleotides. This is consistent with our previous studies [88, 89] and it is suggested that ssRNA is chain wrapping around the tetracationic bis‐triarylborane motif like a thread around a spindle.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All four compounds bind to dsDNA/RNA and ssDNA/RNA with similar affinities; this contrasts with the fact that binding affinities for single‐stranded polynucleotides are typically 2–3 orders of magnitude lower than for double‐stranded polynucleotides. This is consistent with our previous studies [88, 89] and it is suggested that ssRNA is chain wrapping around the tetracationic bis‐triarylborane motif like a thread around a spindle.…”
Section: Discussionsupporting
confidence: 93%
“…The three compounds with longer linkers ( 3 – 5 ) all strongly stabilized the dsDNA/RNA even at rather low ratios of compound to polynucleotide (in the following, this ratio is generally given as: r [compound]/[polynucleotide] ; Figures S27–S35), with anthracene analogue 5 causing the strongest stabilization (Table 2). Our previously reported bithiophene compound 1 [88] and buta‐1,3‐diyne compound 2 [89] stabilized DNA and RNA to a similar extent (Δ T m =7–10 °C). Intriguingly, the short anthracene compound 6 had a very weak effect on the thermal stability of DNA/RNA (Figures S36 and S37).…”
Section: Resultsmentioning
confidence: 70%
“…Triarylboranes are of current interest due to their potential applications in various fields, such as non‐linear optics, [1] live cell imaging, [2a–d] DNA/RNA/protein binding, [2e,f] anion sensors, [3] frustrated Lewis pairs (FLPs), [4] etc., [5] with their properties resulting from the vacant p z orbital on the 3‐coordinate boron atom. This vacant p z orbital can be attacked by nucleophiles, thus 3‐coordinate boranes have been widely used as Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…Todd embraces diversity not only in his group members and numerous local and international collaborators, but also in his research interests [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. For over 30 years, a significant part of his research has focused on metal-catalyzed borylation reactions, metal boryl complexes, mechanisms of borylation and other catalytic reactions [ 1 , 2 , 3 , 4 , 5 , 6 ], and the development of diboron(4) compounds and their chemistry [ 7 , 8 , 9 ].…”
mentioning
confidence: 99%
“…One of the diboron(4) compounds he developed in collaboration with Prof. N. C. Norman (Bristol University), namely B 2 neop 2 , is now available commercially world-wide and is produced in multi-ton quantities. He also works in the fields of conjugated organometallic [ 10 ], organoboron [ 11 , 12 , 13 , 14 , 15 , 16 ] and organic materials [ 17 , 18 , 19 ] for linear and nonlinear optics, 2-photon excited fluorescent cell imaging [ 15 ], DNA/RNA/protein sensing [ 16 ], and on crystal engineering using perfluoroarene-arene interactions [ 20 ], among other areas, often combining several areas of his research in a single project.…”
mentioning
confidence: 99%